2013
DOI: 10.1177/0883073813494474
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Anti-N-Methyl-D-Aspartate (NMDA) Receptor Encephalitis

Abstract: Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is characterized by acute- or subacute-onset encephalopathy with extrapyramidal, psychiatric, and epileptic manifestations. Diagnosis is confirmed by positive antibodies to NMDA receptor in cerebrospinal fluid and serum. Eleven pediatric cases presented over a 2-year period at a tertiary care teaching hospital in North India. The average age at presentation was 9 years (range: 2.5 to 18 years, median: 10 years) with a slight female predominance (1.2:1). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[910] Treatment options are plasmapheresis, steroids, IVIGs, second-line immunomodulators when first line fails, and tumor removal whenever detected. [1112] The antibodies could be present or absent in the serum, CSF, or both, and therefore both need to be examined at least at the first instance. [131415]…”
Section: Anti-nmdar Antibody Syndromementioning
confidence: 99%
“…[910] Treatment options are plasmapheresis, steroids, IVIGs, second-line immunomodulators when first line fails, and tumor removal whenever detected. [1112] The antibodies could be present or absent in the serum, CSF, or both, and therefore both need to be examined at least at the first instance. [131415]…”
Section: Anti-nmdar Antibody Syndromementioning
confidence: 99%
“…There are very few studies of AIE in children reported from India[56] and this is the first clinical series of seronegative AIE. Antibody-negative AIE behaves similarly in the initial clinical presentation, response to immunotherapy and long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…59 A North Indian study of 11 children with NMDAR-AbE reported significant response to steroids and immunoglobulin in 58% of patients. 60 In a prospective Indian study of 15 patients aged 2-64 years with AIE, 67% of patients who were treated with IVIG, steroids or both showed significant improvement, with no further seizures or clinical relapse years at follow-up. 61 A single-arm, open-label study of 41 adult patients with possible autoimmune encephalitis demonstrated a clinical benefit from IVIG with significant improvement in neurological functional outcomes following IVIG treatment.…”
Section: Intravenous Immunoglobulin In Autoimmune Encephalitismentioning
confidence: 99%